The Influence of Product Quality, Price, and Service Quality in Customer Loyalty at PT. Cybernetic Makmur Lestari - Arie Pratania Putri; Alexander Wongkar; Michael Michael; Muhammad Rizki Balliansa (Budapest International Research and Critics University, 2020)
The aims of this study is to fin out the Influence of Product Quality, Price, and Service Quality in Customer Loyalty at PT. Cybernetic Makmur Lestari. This study used qualitative method. The partial test results product quality variable (X1) has a positive and significant effect on consumer loyalty (Y) at PT. Cybernetic Makmur Lestari.The partial test results variable price (X2) has a positive and significant effect on consumer loyalty (Y) at PT. Cybernetic Makmur Lestari. The partial test results service quality variable (X3) has a positive and significant effect on consumer loyalty (Y) at PT. Cybernetic Makmur Lestari. The simultaneous test results of variable product quality (X1) price (X2) and service quality (X3) simultaneously have a positive and significant effect on consumer loyalty at PT. Cybernetic Makmur Lestari amounted to 55.7% and the remaining 44.3% varied by other factors that were not researched such as location, personal selling, and physical evidence.